PDF Hacks - Steward, Sid (O'Reilly Media, Inc., 2004)
PDF--to most of the world it stands for that rather tiresome format used for documents downloaded from the web. Slow to load and slower to print, hopelessly unsearchable, and all but impossible to cut and paste from, the Portable Document Format doesn't inspire much affection in the average user. But PDFs done right is another story. Those who know the ins and outs of this format know that it can be much more than electronic paper. Flexible, compact, interactive, and even searchable, PDF is the ideal way to present content across multiple platforms. PDF Hacks unveils the true promise of Portable Document Format, going way beyond the usual PDF as paged output mechanism. PDF expert Sid Steward draws from his years of analyzing, extending, authoring, and embellishing PDF documents to present 100 clever hacks--tools, tips, quick-and-dirty or not-so-obvious solutions to common problems. PDF Hacks will show you how to create PDF documents that are far more powerful than simple representations of paper pages. The hacks in the book cover the full range of PDF functionality, from the simple to the more complex, including generating, manipulating, annotating, and consuming PDF information. You'll learn how to manage content in PDF, navigate it, and reuse it as necessary. Far more than another guide to Adobe Acrobat, the book covers a variety of readily available tools for generating, deploying, and editing PDF. The little-known tips and tricks in this book are ideal for anyone who works with PDF on a regular basis, including web developers, pre-press users, forms creators, and those who generate PDF for distribution. Whether you want to fine-tune and debug your existing PDF documents or explore the full potential the format offers, PDF Hacks will turn you into a PDF power user.